Matrix metalloproteinases in human spontaneous intracerebral hemorrhage: an update - Florczak-Rzepka, Małgorzata; Grond-Ginsbach, Caspar; Steiner, Thorsten (Cerebrovascular diseases, 2012)
In default of a plausible and satisfactory causal treatment for hemorrhagic stroke, a role of matrix metalloproteinases (MMPs) in the pathogenesis of cerebrovascular diseases has recently been widely discussed. The well-known impact of MMPs on extracellular matrix destruction triggered by inflammation as a foundation for several diseases, including stroke, is very much in evidence. Newly, some additional aspects of MMP function considering their intracellular activity crucial for neuronal death following ischemic brain damage have emerged. The effect of blood-brain barrier disruption caused by MMPs on the prognosis in patients suffering from spontaneous intracerebral hemorrhage (ICH) has been of interest since it throws a new light upon the pathogenesis, course and possible therapeutic approaches for this least treatable and at the same time most life-threatening form of stroke. Hence, we primarily aimed to review the current clinical knowledge on the significance of metalloproteinase activation in the course of spontaneous intracranial hemorrhage in humans. We also provide a brief characterization of the MMP enzyme family and report on the latest findings on issues arising from experimental studies. Methods: A Medline search using the following key words was performed: matrix metalloproteinases + spontaneous intracerebral hemorrhage/intracranial hemorrhage/bleeding/hemorrhagic stroke. We accepted studies reporting on MMP expression in adult patients with spontaneous ICH, as well as its relation to radiological and clinical features and patients’ outcome. For the final review, 18 clinical studies were considered. MMP inhibition was reviewed on the basis of 11 relevant experimental studies. Also, some relevant reports on the biology of MMPs and their pathophysiology in ICH were reviewed. Results and Conclusions: Many studies provide convincing evidence of a detrimental role of MMPs in ICH, stressing their association with neuroinflammation. The role of MMPs in hemorrhagic stroke appears critical for hematoma and brain edema growth as well as for neuronal death, which are understood as secondary brain injury and may have a considerable clinical impact. Although data on human spontaneous ICH are scarce and mostly based on small populations, they reveal the apparent correlation between MMPs and clinical and radiological ICH features as well as the functional outcome, which might rationalize future therapeutic strategies. However, attempts at MMP inhibition in spontaneous ICH have solely been made under experimental conditions and were associated with a wide range of possible side effects. Therefore, further comprehensive, elucidating investigations in this field are vital before any conclusions could be translated to humans.